Pengaruh Land Application Limbah Cair Pabrik Kelapa Sawit terhadap Kadar Nitrogen Dalam Tanah dan Tanaman Kelapa Sawit Menghasilkan - Zaenal Mutaqin; Muliani Muliani; Jaini Fakhrudin; Okto Ivansyah; Nelson Fernando Siahaan (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2022)
This study aims to determine the effect of Palm Oil Mill Effluent (POME) and NPK with various treatment doses on the content of N-total, N-NH4 +, N-NO3 -soil and N uptake of oil palm crops produced. Knowing the appropriate doses of POME and NPK and their interactions for N-total, N-NH4 +, N-NO3 – and N uptake of oil palm crops produce. This research design used a randomized block design (RBD) factorial with 25 treatments and five replicates. The first factor, namely L (POME) consists of 5 levels of treatment, namely: L0 (0 liter of POME / biopore hole), L1 (2.5 liters of POME / biopore hole), L2 (5.0 liters of POME / biopore hole), L3 (7.5 liters of POME / biopore hole) and L4 (10.0 liters of POME / biopore hole). The second factor, namely P (NPK fertilizer 15:15:15) consists of 5 levels of treatment, namely: P0 (0 kg NPK / plant), P1 (0.5 kg NPK / plant), P2 (1.0 kg NPK / plant), P3 (1.5 kg NPK / plant) and P4 (2.0 kg NPK / plant). The results of this study showed that there was an interaction between the dose of POME and the dose of NPK on N-total soil in the oil palm plantation produced. POME self-treatment has a marked effect on the total soil and the uptake of N-producing oil palm crops. NPK self-treatment had a marked effect on the N-total soil and N uptake of oil palm crops resulted in a treatment of 10 liters of POME and 2 kg of NPK was the best treatment against the increase in total N-total, N-NH4 +, N-NO3 - soil and N uptake of plants.